Increased ghrelin and decreased leptin levels in patients with antisocial personality disorder - Tasci, Gulay; Kaya, Suheda; Kalayci, Mehmet; Atmaca, Murad (Elsevier, 2022)
Objective: The study aimed to compare acyl ghrelin (AG), des-acyl ghrelin (DAG), and leptin levels considered to be used as biological markers in the etiopathogenesis of antisocial personality disorder (ASPD) with healthy controls, and to investigate the relationship between these hormones and aggression and impulsivity. Method: The study included 45 patients with ASPD and 61 healthy people in the control group. Sociodemographic data form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Barratt Impulsiveness Scale (BIS-11), and Buss-Durkee Aggression Scale (BDAS) were applied to all participants. Fasting venous blood samples were taken from all participants at the same time of the day and the height and weight of the participants were measured. Results: It was found that the mean serum AG and DAG levels were significantly higher than that of healthy controls whereas leptin hormone levels were significantly lower in patients compared to healthy controls. BDI, BAI, BIS-11, and BDAS scores of the patients were significantly higher compared to healthy controls. There was a positive correlation between AG and DAG hormone levels and impulsivity and aggression. Discussion: The present study is the first in the literature to examine AG, DAG, and leptin hormone levels of patients diagnosed with ASPD. According to the results of the study, it is believed that changes in serum leptin and ghrelin levels will bring a new perspective in terms of understanding the pathophysiological mechanism of ASPD. Further studies are required to explain the definitive roles of these hormones in ASPD.
Keywords: Antisocial personality disorder; Ghrelin; Leptin; Impulsivity; Aggression